2014
DOI: 10.1093/jac/dku080
|View full text |Cite
|
Sign up to set email alerts
|

Suramin is a potent and selective inhibitor of Mycobacterium tuberculosis RecA protein and the SOS response: RecA as a potential target for antibacterial drug discovery

Abstract: Our findings suggest a strategy to chemically disrupt the vital processes controlled by RecA and hence the promise of small molecules for use against drug-susceptible as well as drug-resistant strains of M. tuberculosis for better infection control and the development of new therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 42 publications
1
63
0
Order By: Relevance
“…In the absence of c‐di‐AMP, it was found that > 95% of RecA nucleoprotein filaments exhibit an extended filamentous structure, suggesting cooperative polymerization of RecA (Fig. A); this is, consistent with the characteristic features reported for EcRecA‐ssDNA filaments by AFM visualization (Nautiyal et al, ). Under similar conditions, c‐di‐AMP causes substantial disruption and shrinkage of MtRecA‐ssDNA and MsRecA‐ssDNA filaments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of c‐di‐AMP, it was found that > 95% of RecA nucleoprotein filaments exhibit an extended filamentous structure, suggesting cooperative polymerization of RecA (Fig. A); this is, consistent with the characteristic features reported for EcRecA‐ssDNA filaments by AFM visualization (Nautiyal et al, ). Under similar conditions, c‐di‐AMP causes substantial disruption and shrinkage of MtRecA‐ssDNA and MsRecA‐ssDNA filaments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These findings have been supported genetically, as deletion of SOS response genes enhances drug susceptibility [11,16], while over-expression of mismatch repair genes confers protection [16,33]. Moreover, biochemical inhibition of RecA with polysulfonated compounds potentiates the lethality of multiple antibiotics against both Gram-negative and Gram-positive bacteria [61,62]. Oxidative damage to the nucleotide pool may, in part, underlie this phenotype [29], as incorporation of 8-oxo-guanine induces mismatch repair defects that trigger the formation of double-stranded DNA breaks [16].…”
Section: Bactericidal Processesmentioning
confidence: 99%
“…Examples of suppressors of the SOS response induced by fluoroquinolones were reported in Gram-positive and Gram-negative bacteria, such as the polyphenols baicalein (24), curcumin (25), and suramin (polysulphonated naphthylurea) (26), which have the ability to disassemble RecA single-stranded DNA filaments. Novobiocin blocks the ATP-binding site of the GyrB and inhibits ciprofloxacin and UV-induced SOS response (27,28).…”
mentioning
confidence: 99%